Factors influencing emotional and behavioral problems in preschool children with cancer based on self-regulation shift theory. (July 2022) - Pan, Xiaorong; Mo, Lin; Liu, Qian; Guo, Xiaoli; Zhang, Shiqun
Objective: The objective is to investigate the factors influencing emotional and behavioral problems in preschool children with cancer and to provide a scientific basis for developing predictive intervention strategies. Methods: We recruited 375 preschool children with cancer, from March 2019 to February 2020, via convenience sampling. The self-regulation shift theory was implemented as a theoretical framework and a structural equation model was applied to construct and validate this framework and to analyze the relationships among various influencing factors. Results: Children's effortful control, parent–child attachment, the family environment, family upbringing, parents' marital quality, parents' education level, and social support significantly affected children's emotions and behaviors. Additionally, children's effortful control and parent–child attachment mediated the effect of the family environment, family upbringing, and parents' marital quality on children's emotions and behaviors." Conclusion: This study identified several factors that influence children's emotions and behaviors, which should be considered while developing predictive intervention strategies to promote children's rehabilitation and improve parents' education, thus offering improved support for children with cancer.